Fortalecimiento del pensamiento crítico a través de los dilemas morales : una estrategia pedagógica para la dinamización de los procesos de convivencia en el grado octavo de la I.E.D Eduardo Santos (2017)
The present work constitutes a first link of the processes that are beginning to weave in the Educational Institution Eduardo Santos, seeking to strengthen the critical thinking of the students, to train citizens of the future with principles of integrity, concern for the good Of the other and social justice. It seeks to contribute to the processes of cultural and social development processes of the institution, where the acts of interrelation that emerge within the classroom provide the opportunity of participation and free speech as evidence of reflection through moral dilemmas. For IED Eduardo Santos it is of great importance to promote methods that generate legitimate opportunities to achieve environments that allow the exercise of Human Rights of the student population of the educational establishment. Therefore, this research was designed and implemented a mechanism to strengthen democratic dynamism, in order to transcend in the community with the practice of these exercises...